Perbandingan Prosedur Pengangkatan Anak Menurut Hukum Positif Indonesia Dengan Hukum Islam - Arya Pradana Putra; H. E. Rakhmat Jazuli (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
There are various law systems in Indonesian civil law system. This kind of condition makes child adoption could use one of the governing law systems. This research is focusing on finding civil law systems that is actively governing in Indonesia and comparing the child adoption law between Islamic law and Indonesian civil law. This research uses normative-comparative approach, descriptive method, secondary data, and qualitative analysis. The result of this research shows that at least there two civil law systems in Indonesia, they are Islamic civil law (which uses Islamic Law Compilation) and Indonesian civil law (which uses various regulations made by the Indonesian parliament and government). Child adoption is regulated in Indonesian civil law and legally implicated to all parties involved. On the other hand, child adoption is not allowed in Islamic law. So that, child adoption in Islamic law will have no legal consequences to every parties involved, except the obligatory testament.